The Impact of Peer Mentoring on Loneliness, Depression, and Social Engagement in Long-Term Care. (September 2021) - Theurer, Kristine A.; Stone, Robyn I.; Suto, Melinda J.; Timonen, Virpi; Brown, Susan G.; Mortenson, W. Ben
Loneliness, depression, and social isolation are common among people living in long-term care homes, despite the activities provided. We examined the impact of a new peer mentoring program called Java Mentorship on mentees' loneliness, depression, and social engagement, and described their perceptions of the visits. We conducted a mixed-methods approach in 10 homes in Ontario, Canada, and enrolled residents as mentees ( n = 74). We used quantitative surveys and qualitative interviews to understand their experience. After 6 months, mentees ( n = 43) showed a 30% reduction in depression ( p = .02, d = .76), a 12% reduction in loneliness ( p = .02, d = .76), and a 60% increase in the number of monthly programs attended ( p = .01, d = .37), with small-to-medium effect sizes. The analysis of mentee's interviews revealed positive perceptions. This program offers an innovative, nonpharmacological alternative to the treatment of loneliness and depression.